DUX4-induced bidirectional HSATII satellite repeat transcripts form intranuclear double-stranded RNA foci in human cell models of FSHD. (19th October 2019) - Shadle, Sean C; Bennett, Sean R; Wong, Chao-Jen; Karreman, Nancy A; Campbell, Amy E; van der Maarel, Silvère M; Bass, Brenda L; Tapscott, Stephen J
Abstract: The DUX4 transcription factor is normally expressed in the cleavage-stage embryo and regulates genes involved in embryonic genome activation. Misexpression of DUX4 in skeletal muscle, however, is toxic and causes facioscapulohumeral muscular dystrophy (FSHD). We recently showed DUX4-induced toxicity is due, in part, to the activation of the double-stranded RNA (dsRNA) response pathway and the accumulation of intranuclear dsRNA foci. Here, we determined the composition of DUX4-induced dsRNAs. We found that a subset of DUX4-induced dsRNAs originate from inverted Alu repeats embedded within the introns of DUX4-induced transcripts and from DUX4-induced dsRNA-forming intergenic transcripts enriched for endogenous retroviruses, Alu and LINE-1 elements. However, these repeat classes were also represented in dsRNAs from cells not expressing DUX4. In contrast, pericentric human satellite II (HSATII) repeats formed a class of dsRNA specific to the DUX4 expressing cells. Further investigation revealed that DUX4 can initiate the bidirectional transcription of normally heterochromatin-silenced HSATII repeats. DUX4-induced HSATII RNAs co-localized with DUX4-induced nuclear dsRNA foci and with intranuclear aggregation of EIF4A3 and ADAR1. Finally, gapmer-mediated knockdown of HSATII transcripts depleted DUX4-induced intranuclear ribonucleoprotein aggregates and decreased DUX4-induced cell death, suggesting that HSATII-formed dsRNAs contribute to DUX4 toxicity.